The Development of Academic Identity in Community Schools - Azcoitia, Carlos M. (European Scientific Journal, ESJ, 2017)
This article explores the development of academic identity in community schools. It highlights examples of program and services in different school districts in the United States. It also describes different components of effective community schools and how the community is integrated in the life of the school. It uses a case study approach of John Spry Community School in Chicago. Community schools provide on-going learning for all members of the school community. They provide an alignment of systems that foster a productive, collaborative and culturally responsive culture with high academic growth for all learners. All educational stakeholders including parents and community members accept and follow-up with shared accountability standards. This article substantiates effective practices which promote the full participation of the school community in programs and activities.